From Turf to Table: Grass Seed to Edible Grains in the Willamette Valley - Katlyn Giombolini; Kimberlee Chambers; Joe Bowersox; Peter Henry (Journal of Agriculture, Food Systems, and Community Development, 2016)
Western Oregon's Willamette Valley has a rich history of agricultural production and, like an increasing number of regions globally, a growing local food movement. Recent declines in grass seed markets and an increased consumer interest in local grains have raised the possibility of a transition from grass seed land to edible grain production for local markets. We used geographic information systems (GIS) to determine if the Willamette Valley population's dietary grain needs could be met if current grass seed land were converted to production of soft white winter wheat. In order to explore transitional obstacles and opportunities, we conducted interviews with local farmers, a wholesaler, an agriculture extension worker, and seed developers. The GIS analysis indicated that such a transition could exceed the recommended grain needs of the region's 2008 population. The interviews revealed technical and cultural aspects of transitioning from grass seed production to wheat and other edible crops, identifying insufficient infrastructure (storage, processing, distribution, and market outlets) as the primary barrier to producing for local markets. This combination of GIS analysis (predictive of the food-producing capacity of a region) with in-depth contextual information and practical insights from farmers' voices provides a robust model for planners seeking to analyze and address local food system challenges and possibilities. Our research, while focusing on the Willamette Valley's transition toward a more locally based food system, explores the potential steps for any region looking to transition from nonedible to edible crop production for local consumption.